2017
DOI: 10.1016/j.ydbio.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 and γ-secretase regulate sensory regeneration in the avian vestibular organs

Abstract: The loss of sensory hair cells from the inner ear is a leading cause of hearing and balance disorders. The mammalian ear has a very limited ability to replace lost hair cells, but the inner ears of non-mammalian vertebrates can spontaneously regenerate hair cells after injury. Prior studies have shown that replacement hair cells are derived from epithelial supporting cells and that the differentiation of new hair cells is regulated by the Notch signaling pathway. The present study examined molecular influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Studies in birds and mammals have shown that replacement hair cells can be derived from the supporting cells that remain after hair cell loss through inhibition of the Notch-signalling pathway ( Daudet et al, 2009 ; Lin et al, 2011 ; Warchol et al, 2017 ). To test the hypothesis that hair cell regeneration in human inner ear tissue could be induced by inhibition of Notch signalling, we maintained gentamicin treated cultures (N = 7) in TAPI-1 for 18 days.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in birds and mammals have shown that replacement hair cells can be derived from the supporting cells that remain after hair cell loss through inhibition of the Notch-signalling pathway ( Daudet et al, 2009 ; Lin et al, 2011 ; Warchol et al, 2017 ). To test the hypothesis that hair cell regeneration in human inner ear tissue could be induced by inhibition of Notch signalling, we maintained gentamicin treated cultures (N = 7) in TAPI-1 for 18 days.…”
Section: Resultsmentioning
confidence: 99%
“…Early investigations of aminoglycoside otopathology in animal models focused upon hair cells as the primary targets ( Wersall and Hawkins, 1962 ; Lindeman, 1969a ; Wersall et al, 1969 ; Watanuki et al, 1972 ). Since then, aminoglycosides have been widely used as research tools to lesion vestibular epithelia in investigations of the cellular and molecular mechanisms of hair cell regeneration ( Weisleder and Rubel, 1992 ; Forge et al, 1993 ; Weisleder and Rubel, 1993 ; Lopez et al, 1999 ; Popper et al, 1999 ; Stone and Rubel, 2000 ; Dickman and Lim, 2004 ; Stone et al, 2004 ; Lyford-Pike et al, 2007 ; Haque et al, 2009 ; Kawamoto et al, 2009 ; Warchol, 2010b ; Burns and Corwin, 2014 ; Warchol et al, 2017 ). Additionally, gentamicin is an agent commonly used in investigations of mammalian vestibular pathophysiology ( Imamura and Adams, 2003a , b ; Hirvonen et al, 2005 ; Hong et al, 2006 ; Day et al, 2007 ; Lue et al, 2009 ; Ding et al, 2010 ; Warchol, 2010a ; Bremer et al, 2014 ; King et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms that trigger the onset of avian hair cell regeneration by either process are unknown. Despite identification of signaling pathways potentially involved in hair cell regeneration (Alvarado et al 2011;Ku et al 2014;Warchol et al 2017), a thorough mechanistic insight of regeneration from the earliest events of initiation, realization, and ultimately termination is not known. Moreover, in vivo experiments to investigate regeneration require repeated systemic injections of ototoxic aminoglycoside to induce reliable hair cell loss throughout the utricle (e.g., Cafaro et al 2007), which makes it difficult to define the precise dosage or onset of injury.…”
Section: Introductionmentioning
confidence: 99%